2020
DOI: 10.1017/wet.2020.104
|View full text |Cite
|
Sign up to set email alerts
|

PRE- and POST-applied herbicide options for alfalfa interseeded with corn silage

Abstract: Establishment of alfalfa by interseeding into corn planted for silage can enhance crop productivity but weed management is a challenge to adoption. Although a glyphosate-based herbicide program could be a simple and effective approach, concerns about herbicide resistance and limitations in available alfalfa varieties exist. Field experiments were conducted to compare the efficacy and selectivity of preemergence (PRE), postemergence (POST) and PRE followed by POST herbicide programs to a glyphosate only strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…Successful establishment of forage legumes in a maize-silage companion crop for subsequent forage production appears to be highly dependent on management practices, growth environment, and the developmental characteristics and yield potential of maize. Multi-year studies in Wisconsin, USA demonstrated that alfalfa establishment in maize silage is favored by early interseeding prior to the V2 stage of maize using normal alfalfa seeding rates, and by planting maize at moderate maize populations to lessen competition and allow some penetration of direct sunlight to alfalfa seedlings following maize canopy closure [132][133][134][135]. Establishment of interseeded alfalfa in Wisconsin was further enhanced by planting a suitable variety [136] and by treating seedlings with the gibberellin inhibitor prohexadione followed by fungicide and insecticide to promote root growth and overall plant health [132][133][134]136].…”
Section: Perennial Forages Intercropped or Interseeded With Annual Cropsmentioning
confidence: 99%
See 2 more Smart Citations
“…Successful establishment of forage legumes in a maize-silage companion crop for subsequent forage production appears to be highly dependent on management practices, growth environment, and the developmental characteristics and yield potential of maize. Multi-year studies in Wisconsin, USA demonstrated that alfalfa establishment in maize silage is favored by early interseeding prior to the V2 stage of maize using normal alfalfa seeding rates, and by planting maize at moderate maize populations to lessen competition and allow some penetration of direct sunlight to alfalfa seedlings following maize canopy closure [132][133][134][135]. Establishment of interseeded alfalfa in Wisconsin was further enhanced by planting a suitable variety [136] and by treating seedlings with the gibberellin inhibitor prohexadione followed by fungicide and insecticide to promote root growth and overall plant health [132][133][134]136].…”
Section: Perennial Forages Intercropped or Interseeded With Annual Cropsmentioning
confidence: 99%
“…Multi-year studies in Wisconsin, USA demonstrated that alfalfa establishment in maize silage is favored by early interseeding prior to the V2 stage of maize using normal alfalfa seeding rates, and by planting maize at moderate maize populations to lessen competition and allow some penetration of direct sunlight to alfalfa seedlings following maize canopy closure [132][133][134][135]. Establishment of interseeded alfalfa in Wisconsin was further enhanced by planting a suitable variety [136] and by treating seedlings with the gibberellin inhibitor prohexadione followed by fungicide and insecticide to promote root growth and overall plant health [132][133][134]136]. A similar study conducted in North Dakota had similar results to those of Grabber [132] but application of prohexadione did not improve alfalfa survival [137].…”
Section: Perennial Forages Intercropped or Interseeded With Annual Cropsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous results are inconsistent regarding the impact of weed control on alfalfa forage yield [32], but more consistently indicate reductions in nutritive value from weed pressure. Weed control programs were also found not to impact total biomass accumulation in a corn silage and alfalfa system [52].…”
Section: Weed Density and Communitymentioning
confidence: 92%
“…In this system, alfalfa is interseeded to serve as a highly effective cover crop for corn, and then it is brought into full forage production the following year. The successful interseeding of alfalfa reduces the risk of soil and nutrient loss from cropland, suppresses weeds, and increases the overall forage yields and profitability of corn silage-alfalfa rotations [8][9][10][11][12][13][14][15]. Full realization of these benefits will, however, require the reliable establishment of alfalfa while maintaining relatively high yields of the corn companion crop [10].…”
Section: Introductionmentioning
confidence: 99%